Rheological Behavior of Air in the Two-Pass Solar Collector - Dhaundiyal, Alok (Frontiers in Energy Research, 2022)
The paper pivoted on the flow behaviour of air streams across the solar air collectors provided with the wooden baffles under the absorber plates. The two-pass system was used for both flat and finned surfaces. The von Karman momentum integral equation and Blasius equation were solved with the help of PDPE and ODE45 techniques. The solution was assumed to be a part of the initial value problem (IVP). The energy analysis of both solar air collectors was carried out using the Hottel-Whillier-Bliss equation (HWB) equation. The Sankey diagram was used for energy distribution across the solar collectors. The grey box modelling approach was adopted to comprehend the airflow behaviour across the channel. The objective of this paper is to examine the intrinsic behaviour of the proposed design. The displacement of boundary to compensate for the momentum of air stream (θt) was decreased by 31.25–62.50% with an increase in mass flow rate ((m)) ̇ by 24.69–49.38% for flat plate collector (FPC). Similarly, the shear stress posed by the absorber plate (τw) was dropped by 15.89–37.20% with the augmentation of the mass flow rate. Relatively, the momentum thickness for the flat plate with triangular fin (FPTF) was increased by 31.25%, as compared to FPC at 8.10 g·s−1. The estimated value of collector efficiency (ηI) FPTF was soared up by 4–11.51% when it was juxtaposed with the corresponding values derived for FPC. The wall shear stress near the absorber plate would follow a second-order Gaussian model. It was noticed in this study that the addition of fin has slowed down the shear effect and the momentum defect of airstream at the same mass flow rate.